A atividade pedagógica como estratégia de motivação : implicações no desempenho de alunos surdos na produção escrita em língua portuguesa - Silva, Maria Auxiliadora Baggio da (2007)
The motivation is one of the most important factors in the acquisition process of a second language. The use of motivational strategies in the classroom may constitute a great auxiliary in the task of arouse and keep the student´s motivation in the learning of L2. A proposal of Portuguese teaching as L2 for deaf students must consider the pedagogical activities as part of these motivational strategies. The use of pedagogical activities as motivational strategy will increase the motivation for Portuguese learning and bring a better performance of the students in the writting of this language. In order to empirically prove these hypothesis, an experimental research was developed with two highschool classes of deaf students. The teorical basis of this assignment takes place on the contributions of Applied Psycholinguistic, Text Linguistic and Projects Education. The research results show that although the use of pedagogical activities as motivation instrument hasn t influenced on the motivation increase for Portuguese learning, its use implied a significant improvement on the composing performance of the experimental group´s students, in which the strategies were applied, compared with the performance of the control group´s students.